1997
DOI: 10.1620/tjem.183.67
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Rises in Urinary Bicarbonate Contents and pH Related with Increased Atmospheric Carbon Dioxide in Tokyo.

Abstract: Atmospheric carbon dioxide concentration was measured at several locations in Tokyo, for two weeks, in December, 1995 and 1996, and was found to be increased up to 550 ppm, while it was shown by us to be 450 ppm in December, 1994. These results demonstrate that atmospheric carbon dioxide is steadily increasing at faster rates in Tokyo than we expect, though it has been considered that the atmospheric carbon dioxide is still as much as 350 ppm. Bicarbonate concentration and pH of urine of 13 medical students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The present results suggest that the measurement of urinary bicarbonate and urinary pH will be useful to evaluate the acid-base balance in subjects exposed to high concentrations of atmospheric CO2 (Tomoda et al 1995(Tomoda et al , 1997, or with increased amounts of endogeneous CO2 in the blood after heavy exercise such as submaximal cycling exercise.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The present results suggest that the measurement of urinary bicarbonate and urinary pH will be useful to evaluate the acid-base balance in subjects exposed to high concentrations of atmospheric CO2 (Tomoda et al 1995(Tomoda et al , 1997, or with increased amounts of endogeneous CO2 in the blood after heavy exercise such as submaximal cycling exercise.…”
Section: Discussionmentioning
confidence: 87%
“…Pitts et al (1949) indicated that the excretion of titrable acid into urine decreases according to the increase of discharged amounts of bicarbonate into the urine from the blood, which is consistent with the view that during hypercapnea, bicarbonate will accumulate in the blood, resulting in discharge of bicarbonate into the urine and leftover hydrogen ion in the blood; thereby, causing acute respiratory acidosis. In 1990, Tomoda et al (1995Tomoda et al ( , 1997 reported that a large amount of bicarbonate was discharged into the urine accompanying the urinary alkalization in subjects who were confined to enclosed rooms or cars with closed windows and who inspired higher concentrations of CO2 for 3 hours or so. This result was explained by the fact that the increased CO2 in the blood was converted to bicarbonate and hydrogen ion by erythrocytic carbonic anhydrase, and the excessively produced bicarbonate was discharged into the urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation